Transformasi Digital UMKM Perikanan: Studi Kasus Poklahsar Bali Padang - Aisyah, Siti; Putra, Ari Limay Trisno; Sari, Siska Fitrima; Desmiati, Ira; Rustam, Dicky (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2025)
Abstract: This community service program was implemented with POKLAHSAR BALI, a fisheries MSME in Ulak Karang Utara, Padang City, whose members are mostly women and coastal youth. The main problems identified were traditional production methods, unstructured business management, and marketing dependence on collectors, limiting added value. The program aimed to improve production capacity, strengthen business governance, and develop a website-based digital marketing strategy. A participatory-collaborative approach was applied through socialization, technical training, technology implementation, mentoring, and continuous evaluation. Innovations introduced included production SOPs, logbooks and simple bookkeeping, a gas-fueled drying oven, development of the website www.sejala.org, QR Code integration on packaging, and activation of social media and marketplaces. Evaluation showed significant improvements in partner skills, with average scores increasing from 2.7 to 4.0, particularly in business recording and digital marketing. Economically, average income rose by 25% and digital sales volume doubled. Sustainability was strengthened through cooperation with the Merah Putih Cooperative and regular coaching from the Padang City Marine and Fisheries Office, thereby enhancing the economic independence of coastal women and youth. Keywords: coastal women’s empowerment; digital marketing; fisheries MSMEs; local food products; padang city; website. Abstrak: Program pengabdian masyarakat ini dilaksanakan bersama POKLAHSAR BALI, sebuah UMKM perikanan di Ulak Karang Utara, Kota Padang, yang mayoritas anggotanya perempuan dan remaja pesisir. Permasalahan utama mitra meliputi metode produksi tradisional, manajemen usaha yang belum tertata, serta pemasaran yang bergantung pada pengepul sehingga nilai tambah terbatas. Program ini bertujuan meningkatkan kapasitas produksi, memperkuat tata kelola usaha, dan mengembangkan strategi pemasaran digital berbasis website. Metode partisipatif-kolaboratif diterapkan melalui sosialisasi, pelatihan teknis, penerapan teknologi, pendampingan, dan evaluasi berkelanjutan. Inovasi yang diperkenalkan meliputi SOP produksi, penggunaan logbook dan pembukuan sederhana, oven pengering berbahan bakar gas, pengembangan website www.sejala.org, integrasi QR Code pada kemasan, serta aktivasi media sosial dan marketplace. Hasil evaluasi menunjukkan peningkatan keterampilan mitra dengan skor rata-rata naik dari 2,7 menjadi 4,0, terutama pada pencatatan usaha dan pemasaran digital. Secara ekonomi, pendapatan meningkat rata-rata 25% dan volume penjualan digital dua kali lipat. Keberlanjutan program diperkuat melalui kerjasama dengan Koperasi Merah Putih dan pembinaan rutin Dinas Kelautan dan Perikanan Kota Padang, sehingga mampu mendukung kemandirian ekonomi perempuan dan remaja pesisir. Kata kunci: kota padang; pemasaran digital; produk pangan lokal; pemberdayaan perempuan pesisir; umkm perikanan; website